Probity Audit as a Mediator of Determinants of Sustainable Public Procurement: A Literature Review - Sopian, Sopian; Djaddang, Syahril (Jurnal Ilmiah Global Education, 2025)
Sustainable Public Procurement (SPP) is one of the stages in the implementation of the realization of the state budget. SPP pays attention to the balance between price, environment and benefits for the community. Many factors can encourage the realization of SPP. This research aims to study the literature on the determinants of SPP from research results that have been published openly. The results of the literature study found that the effectiveness of internal control consisting of elements of competence and independence of internal auditors has a significant influence on SPP. In addition, management support and synergy with external auditors are estimated to have a significant influence on the effectiveness of internal control. Probity audits carried out by internal supervisors are expected to maintain compliance with the procedures for implementing SPP. Management needs to build an independent and credible electronic public procurement system to provide equal opportunities to all prospective vendors so that SPP can be implemented in accordance with the procurement plan and obtain fair prices and quality goods.